Early pushing urge in labour and midwifery practice: A prospective observational study at an Italian maternity hospital - Borrelli, Sara E.; Locatelli, Anna; Nespoli, Antonella (Elsevier, 2013)
OBJECTIVE: to investigate the early pushing urge (EPU) incidence in one maternity unit and explore how it is managed by midwives. The relation to some obstetric outcomes was also observed but not analysed in depth. DESIGN: prospective observational study. SETTING: Italian maternity hospital. SAMPLE: 60 women (44 nullips and 16 multips) experiencing EPU during labour. FINDINGS: the total EPU incidence percentage was 7.6%. The single midwives’ incidences range had a very wide margin, noting an inverse proportion between the number of diagnoses of EPU and midwife’s waiting time between urge to push and vaginal examination. Two care policies were adopted in relation to the phenomenon: the stop pushing technique (n¼52/60) and the ‘let the woman do what she feels’ technique (n¼8/60). In case of stop pushing techniques, midwives proposed several combined techniques (change of maternal position, blowing breath, vocalisation, use of the bath). The EPU diagnosis at less than 8 cm of cervical dilatation was associated with more medical interventions. Maternal and neonatal outcomes were within the range of normal physiology. An association between the dilatation at EPU diagnosis and obstetric outcomes was observed, in particular the modality of childbirth and perineal outcomes. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: this paper contributes new knowledge to the body of literature around the EPU phenomenon during labour and midwifery practices adopted in response to it. Overall, it could be argued that EPU is a physiologic variation in labour if maternal and fetal conditions are good. Midwives might suggest techniques to woman to help her to stay with the pain, such as change of position, blowing breath, vocalisation and use of the bath. However, the impact of policies, guidelines and culture on midwifery practices of the specific setting are a limitation of the study because it is not representative of other similar maternity units. Thus, a larger scale work should be considered, including different units and settings. The optimal response to the phenomenon should be studied, considering EPU at different dilatation ranges. Future investigations could also focus on qualitative analysis of women and midwives’ personal experience in relation to the phenomenon.